MANAJEMEN SISTEM DAN MONITORING PENJUALAN UMKM PADA OUTLET SOMAY BATAGOR CAKRA BUANA - Pane, Eddissyah Putra; Afriansyah, Afriansyah; Juliani, Fitri (Universitas Lancang Kuning, 2025)
UMKM Cakra Buana, which operates more than 11 outlets, still relies on manual record-keeping using report books that are photographed and sent via WhatsApp. This process often leads to data discrepancies and inaccurate calculations. Therefore, an integrated system is needed to enable real-time sales monitoring. This research develops an Android-based information system that integrates sales data from each outlet, allowing management to oversee transactions, sales reports, and inventory. The outcomes of this research include a monitoring application, a scientific journal article, and a teaching module for a web programming course.